Clinical Features, Endoscopic Findings, and Predictive Factors for Mortality in Tissue-Invasive Gastrointestinal Cytomegalovirus Disease between Immunocompetent and Immunocompromised Patients - Panu Wetwittayakhlang; Natthapat Rujeerapaiboon; Poowadon Wetwittayakhlung; Pimsiri Sripongpun; Nannapat Pruphetkaew; Sawangpong Jandee; Naichaya Chamroonkul; Teerha Piratvisuth (Gastroenterology Research and Practice)
Background and Aims. Tissue-invasive gastrointestinal cytomegalovirus (TI-GI CMV) disease is common in immunocompromised patients, but the increasing prevalence in immunocompetent patients has been reported. This study compared the clinical manifestations, endoscopic features, treatment outcomes, and predictors for inhospital mortality of TI-GI CMV between immunocompromised and immunocompetent patients. Methods. Patients with HIV infection, malignancy, or receiving immunosuppressive agents (chemotherapy, high dose, or long-term corticosteroids) were defined as the immunocompromised group. Demographic and inhospital mortality data were obtained and retrospectively analyzed. Results. A total of 213 patients (89 immunocompetent) with histologically confirmed TI-GI CMV were enrolled. Immunocompetent patients were older (70 vs. 52 years; p<0.001), had more GI bleeding as a presenting symptom (47.2% vs. 29.0%; p=0.010), and shorter symptom onset (2 vs. 14 days, p=0.018). Concomitant extra-GI involvement was only seen in the immunocompromised group (6.5% vs. 0%; p=0.02). Diffuse GI tract (14.5% vs. 4.5%; p=0.032) and esophageal involvement (14.5% vs. 5.6%; p=0.046) were more frequent in the immunocompromised, while small bowel involvement was more frequent in the immunocompetent group (19.1% vs. 8.1%; p=0.029). An overall inhospital mortality was 27.7%. There was no significant difference in inhospital survival probability between the two groups (Peto-Peto test, p=0.65). ICU admission (hazard ratio [HR] 7.21; 95% CI 2.55-20.36), sepsis or shock (HR 1.98; 95% CI 1.08-3.66), malnutrition (HR 2.62; 95% CI 1.05-7.01), and receiving chemotherapy (HR 5.2; 95% CI 1.89-14.29) were independent factors for inhospital mortality. Antiviral treatment for more than 14 days was the only protective factor to improve survival (Peto-Peto test, p<0.001). Conclusions. Immunocompetent and immunocompromised patients with TI-GI CMV disease had distinct clinical and endoscopic characteristics. There was no significant difference in the inhospital mortality between the two groups. The factors for mortality were ICU admission, sepsis/shock, malnutrition, and receiving chemotherapy. Early diagnosis and initiation of antiviral treatment might improve the survival probability.